FatVAP: Aggregating AP Backhaul Capacity to Maximize Throughput - Kandula, Srikanth; Lin, Kate; Badirkhanli, Tural; Katabi, Dina (Fifth Networked Systems Design and Implementation (NSDI), 2008)
It is increasingly common that computers in residential and hotspot scenarios see multiple access points (APs). These APs often provide high speed wireless connectivity but access the Internet via independent, relatively low-speed DSL or cable modem links. Ideally, a client would simultaneously use all accessible APs and obtain the sum of their backhaul bandwidth. Past work can connect to multiple APs, but can neither aggregate AP backhaul bandwidth nor can it maintain concurrent TCPs across them. This paper introduces FatVAP, an 802.11 driver that aggregates the bandwidth available at accessible APs and also balances their loads. FatVAP has three key features. First, it chooses the APs that are worth connecting to and connects with each AP just long enough to collect its available bandwidth. Second, it ensures fast switching between APs without losing queued packets, and hence is the only driver that can sustain concurrent high throughput TCP connections across multiple APs. Third, it works with unmodified APs and is transparent to applications and the rest of the network stack. We experiment with FatVAP both in our lab and hotspots and residential deployments. Our results show that, in today’s deployments, FatVAP immediately delivers to the end user a median throughput gain of 2.6x, and reduces the median response time by 2.8x.